Green Metric Based Thin-Layer Chromatography Coupled with Mass Spectrometry to Identify Degradation Products of Lumateperone in Bulk and Formulation - Ghante, Minal; Tangde, Jyoti; Bhusari, Vidhya; Patil, Arpana; Parmar, Payal (International Journal of Pharmaceutical Investigation, 2026)
Objectives The goal of current work was to develop a new, simple, reliable and sensitive High-Performance Thin-Layer Chromatography (HPTLC) method for the estimation of lumateperone. This study also includes the identification of degradation products of lumateperone using different stress conditions and characterization of degradants using mass spectrometry. Materials and Methods The method development was performed using Thin-Layer Chromatography (TLC) plates (pre-coated) with silica gel G 60 F254. The mobile phase comprised ethyl acetate, methanol, toluene and ammonia in a ratio of 4:2:4:0.1 (v/v). Densitometric scanning was carried out at the absorbance mode of 252 nm. Validation was performed according to International Council for Harmonization (ICH Q2R1) guidelines. Results Linearity was achieved in the range of 84-504 ng/band. The calibration curve, R2=0.9994. The Detection Limit (LOD) and Quantification Limit (LOQ) were identified at 3.22 ng/band and 7.78 ng/band. Recovery ranged from 98% to 102%. Forced degradation results of lumateperone show it is susceptible to degradation in acidic, alkaline, oxidative, thermal, photolytic and neutral stressors. Degradation Products (DPs) of acidic, alkaline and thermal conditions were distinguished by High-Resolution Mass Spectrometry (HR-MS). The greenness of method was confirmed by AGREE tool by following the green chemistry principals. Conclusion The result produced by above method is linear, precise and accurate, making it suitable for routine quantification and stability analysis of lumateperone.
Keywords: HPTLC; HR-MS; Lumateperone; Tablet formulation; Validation.